Innovative business development: Identifying and supporting future radical innovators - Sina von der Schmidt; Dietrich Oelsnitz (Leadership, Education, Personality. An Interdisciplinary Journal, 2020)
As the corporate environment becomes more volatile, uncertain, complex and ambiguous, companies are challenged to simultaneously adapt to multiple scenarios, develop radical innovations and destroy past successes. This flexible, i.e. agile and user-oriented, exploration must be ensured by exploiting already established efficiencies ("ambidextry"). However, most German SMEs do not engage in both radical and evolutionary innovations. Therefore, they tend to be disrupted. By investigating existing models regarding vuca-resilience and the development of radical innovations it was found that no practical guideline exists that provides established companies with VUCA-foresight in order to collaborate with radical innovators and thus achieve ambidextry. In order to close that gap, experts of five German companies were interviewed regarding their company's innovation behaviour. Based on the interviews as well as scientific approaches regarding VUCA-resilience and the development of radical innovations a ten-step guideline has been derived. The success of the model has been proofed by three German SMEs that initially pushed little or no radical innovation and subsequently even founded their own company builders. Since this paper only shows the ideal way for established companies to achieve ambidextry with the help of radical innovators, further research is needed to provide solutions for non-ideal cases. Additional validation can be achieved in which the model is not only validated by German SMEs, but also by companies of other sizes and countries.
Keywords: 330; Design driven innovation; Lab; Lean startup; Radical business model innovation; Scenarios; Spin-offs